Development and application of I_SUM : an index of sustainable urban mobility - Silva, Antônio Nélson Rodrigues da (2010)
This work describes the construction process of an Index of Sustainable Urban Mobility (I_SUM). Important aspects regarding its application as a mobility planning and management supporting tool are also discussed. The index is based on a hierarchy of criteria built essentially with data obtained from planners and technicians of eleven cities, what resulted in eighty-seven Indicators forming thirty-seven Themes, under nine Domains. Weights for the Themes and Domains were obtained through a panel of experts. A viability analysis of the index application was carried out in a city with around 220,000 inhabitants located in the state of São Paulo, Brazil. The analysis of the results has shown that a significant number of indicators could be calculated in the short term and with good quality data in the studied city. The main conclusion drawn from the application was the confirmation that I_SUM is flexible enough to be applied not only in a developing country medium-sized city, but also in cities with diverse characteristics. It is important to highlight the fact that the tool also gives the opportunity to assess the relative contribution of any specific aspects of mobility to the Social, Economic, and Environmental dimensions of sustainability. That I_SUM feature can be used to help in the formulation of either integrated or stand-alone policies per sector aiming at the development of the sustainable urban mobility. Moreover, it can help in the public participation process due to the possibility of building up scenarios based on hypothetical changes of the indicator values.